ANÁLISE MULTIMODAL DE LIVROS INFANTIS: UM OLHAR ALÉM DO TEXTO VERBAL - Michelotti, Patricia (2022)
Literature has been, is and tends to increasingly consolidate its role in the education of children, young people, and adults. The mediated society is not limited, however, to books full of verbal text whose gaps must be filled exclusively by imagination. The book is multissemiotic and brings with it many messages, especially the illustrated book of children´s literature. This master's thesis has the general objective of investigating the role of image in the construction of meaning in children’s books of authors illustrators, focusing on multimodality and the pedagogical context. As specific objectives, we intend to apply the Grammar of Visual Design to the study of images in children's books; to identify recurrences regarding the semiotic resources present in the images in the selected children’s books and demonstrate useful categories for the analysis of the image in the children's book, in view of the pedagogical context. For the selection of books, criteria were followed: a) we delimited a sample of three books by illustrators, that is, cases in which the author himself illustrated his story; b) we opted for books that were listed by Crescer Magazine in 2015 (all published in 2014), which listed the 30 best children's literature books of that year; c) we opted for colored books from this list, which were between 15 and 35 pages long and that presented verbal text and visual text images. Our proposal was to work with the Grammar of Visual Design of Kress and van Leeuwen (2006), through a qualitative research, multimodal analysis, analyzing the selected works. To reach our objectives this proposal, this research permeates the theoretical concepts of book such as technology, children's literature, multiliteracies and multimodality. With the result of this work, we demonstrate how the images act in the composition of children’s stories and how the authors-illustrators make their use tied to the purpose and theme of each work. From the application of the GDV, we concluded that verbal and visual text work together. The image acts as complements and extrapolations to the verbal text so that it is impossible to say that one precedes the other. We believe that the result of this work is an important study tool for adult readers, to encourage a complete reading of literary works for children. Through educators that amplifier look, into the classroom, to bring results in the formation of more prepared and critical readers.